2020
DOI: 10.1016/j.isci.2020.101448
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Ubiquitination at Lysine 104 Retains Exchange Factor Regulation by Dynamically Modulating the Conformation of the Interface

Abstract: Summary RAS proteins function as highly regulated molecular switches that control cellular growth. In addition to regulatory proteins, RAS undergoes a number of posttranslational modifications (PTMs) that regulate its activity. Lysine 104, a hot spot for multiple PTMs, is a highly conserved residue that forms key interactions that stabilize the RAS helix-2(H2)/helix-3(H3) interface. Mutation at 104 attenuates interaction with guanine nucleotide exchange factors (GEFs), whereas ubiquitination at lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…To generate the ensemble of conjugated E2 structures, we used the E2 thioester protocol in Rosetta (Saha et al, 2011). This protocol is a tethered docking protocol which we have previously used to construct and analyze the conformational ensemble of conjugated Ub (Yin et al, 2020). We have previously observed that this conjugated docking quickly settles in a local minimum and then remains in that relative orientation.…”
Section: Rosetta Modelingmentioning
confidence: 99%
“…To generate the ensemble of conjugated E2 structures, we used the E2 thioester protocol in Rosetta (Saha et al, 2011). This protocol is a tethered docking protocol which we have previously used to construct and analyze the conformational ensemble of conjugated Ub (Yin et al, 2020). We have previously observed that this conjugated docking quickly settles in a local minimum and then remains in that relative orientation.…”
Section: Rosetta Modelingmentioning
confidence: 99%
“…Clearly, K104 and K147 are solvent exposed and amenable for ubiquitin ligation. We then used a structure of wild-type KRAS described in previous studies , to build four structural models of KRAS monoubiquitinated at K104 (mUbKRAS 104 ) and four models of KRAS monoubiquitinated at K147 (mUbKRAS 147 ). Ubiquitin (Ub) was linked to K104 or K147 via an isopeptide bond as described previously and placed in different orientations relative to KRAS in the four different starting configurations of both mUbKRAS 104 and mUbKRAS 147 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the full-length ubiquitin G76C mutant was expressed in E. coli BL21 (pLysS). Both the proteins were purified as described with protein purity validated using SDS-PAGE. Ubiquitin G76C was ligated to KRAS K104C using a chemical ligation strategy adapted from Baker et al NMR sample preparation and data collection were conducted as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the differences, previous work in the Ras ubiquitylation field allows us to think more critically about our Rap2 findings and future directions (Baker et al 2012(Baker et al , 2013Yin et al 2020;Thurman, Siraliev-Perez, and Campbell 2020). Specifically, mono-ubiquitylation of KRas-K147 impedes GAP-mediated GTP hydrolysis and promotes effector binding (Sasaki et al 2011;Baker et al 2012Baker et al , 2013.…”
Section: Differential Regulation Between Rap and Ras Family Membersmentioning
confidence: 99%